Case report: Recurring potassium channel complex autoimmunity-related neuropathic pain - Zhu, Yun-Qing; Zhou, Xin-Qiao; Yang, Min; Horill, Smita; Wang, Zhong-Yun; Yang, Jian-Jun; Pan, Yin-Bing; Zhou, Xiao-Kai (Frontiers in Immunology, 2024)
Voltage-gated potassium channel (VGKC) complex autoimmunity associated with nerve hyperexcitability is an uncommon clinical spectrum. It is mostly characterized by limbic encephalitis, continuous neuromyotonia and dysautonomia. Pain, however, has rarely been reported as the first symptom. The present study describes a case of persistent neuropathic pain as the only symptom associated with a positive serum contactin-associated protein-like 2 (CASPR2) auto-antibody in a 41-year-old female patient. Her pain was completely relieved with steroids and intravenous immunoglobulin (IVIG) therapy. Nevertheless, the pain recurred 1 year later, consistent with an immunofluorescence titer of the CASPR2 antibody. Our case shows that neuropathic pain may occur as the first and only manifestation of VGKC complex autoimmunity disorder. VGKC antibody titers might be an indication of pain severity. Steroids coupled with IVIG are effective, but relapse may still occur.